LESSONS TO BE LEARNT FROM THE EXTINCTION OF THE “NATIONAL FLOWER” OF SOUTH AFRICA - Werner Scholtz (Obiter, 2022)
The increasing waste problem experienced with plastic bags in South Africa led to the banning of the manufacturing and distribution of thin plastic bags on 9 May 2003 (GN 625 in GG 24839 of 2003-05-09). The promulgation of these regulations was the result of three years of regulatory activity from the side of the Department of Environmental Affairs and Tourism (DEAT) as well as lengthy negotiations between the government, business and labour sectors. The result of these negotiations was the drafting of a Memorandum of Agreement (MOA) between organised business, government and labour, which included areas of agreement in relation to issues such as the minimum thickness of plastic bags. It is interesting to note that the consensus between the parties was not embodied in an Environmental Management Co-operation Agreement (EMCA) as provided for in section 35 of the National Environmental Management Act 107 of 1998 (NEMA).It is the intent of this note to reflect on the manner in which the problem of plastic bags was addressed through the regulatory authority of the Minister of Environmental Affairs and Tourism (the Minister). This note furthermore ascertains whether an EMCA could have been a worthwhile instrument to regulate the issue of plastic bags in South Africa. Some proposals are made in conclusion with regard to the usage of an EMCA as a mechanism to address environmental issues.This ex post facto investigation is of value since lessons for government, business and labour may be distilled from the plastic bags experience. It may in addition be of assistance in the application of solutions for future environmental problems. This note does not undertake an extensive examination of the content of the plastic bag regulations, but rather focuses on the manner in which this issue is regulated as well as the process that was embarked upon prior to the promulgation of the regulations.